2018
DOI: 10.2196/jmir.7618
|View full text |Cite
|
Sign up to set email alerts
|

Digital Gaming for Improving the Functioning of People With Traumatic Brain Injury: Randomized Clinical Feasibility Study

Abstract: BackgroundTraumatic brain injury (TBI) is a major health problem that often requires intensive and long-term rehabilitation.ObjectiveThe aim of this study was to determine whether rehabilitative digital gaming facilitates cognitive functioning and general well-being in people with TBI.MethodsA total of 90 Finnish-speaking adults with TBI (18-65 years) were recruited from an outpatient neuroscience clinic. The participants were randomly allocated to one of the three groups: a rehabilitation gaming group (n=29, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 74 publications
(92 reference statements)
0
10
0
Order By: Relevance
“…In total, 27 RCTs were included in the current review [ 43 - 69 ]. Of those, 16 RCTs were included in the meta-analyses [ 45 - 52 , 54 , 59 - 65 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In total, 27 RCTs were included in the current review [ 43 - 69 ]. Of those, 16 RCTs were included in the meta-analyses [ 45 - 52 , 54 , 59 - 65 ].…”
Section: Resultsmentioning
confidence: 99%
“…In 7 studies, the effect of computerized CBT games was compared with that of no intervention on the severity of depressive symptoms [ 59 - 65 ], and 4 of these studies assessed the effect of a computerized CBT game (SPARX) on the severity of depressive symptoms among patients with depression [ 59 , 60 , 64 ]. The first study found a statistically significant effect of the computerized CBT game over no intervention on the severity of depressive symptoms as measured using the Children’s Depression Rating Scale-Revised (CDRS-R; P =.001) but not the Reynolds Adolescent Depression Scale (RADS-2; P =.08) [ 59 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In total, 27 RCTs were included in the current review . Of those, 16 RCTs were included in the meta-analyses [45][46][47][48][49][50][51][52]54,[59][60][61][62][63][64][65].…”
Section: Search Resultsmentioning
confidence: 99%